Variability of extreme precipitation over Yunnan Province, China 1960–2012. (14th March 2014) - Li, Yun‐Gang; He, Daming; Hu, Jin‐Ming; Cao, Jie
ABSTRACT This study investigated spatial and temporal variations of extreme precipitation over Yunnan Province during 1960–2012. On the basis of a dataset from 120 meteorological stations covering the region, ten precipitation indices derived from daily precipitation were computed and analysed. Our results indicate the precipitation indices showed spatially complex trends. Most precipitation indices present increasing trends in western Yunnan and decreasing trends in eastern Yunnan. The western, southern and central regions experienced an increase in consecutive dry days (CDDs) and decrease in consecutive wet days (CWDs). In addition, a widespread increase was also found in precipitation intensity over Yunnan. On a region‐wide scale, a weak decrease was observed in total precipitation, accompanied by an increase in precipitation intensity. CDDs tended to be prolonged while the CWDs tended to be shortened. The days with precipitation amounts totaling more than 10 mm and maximum 5‐day precipitation amount had decreasing but not significant trends. In contrast, insignificant increases were found for the maximum 1‐day precipitation and annual total precipitation exceeding 95th and 99th percentiles. The contribution of extreme precipitation to total precipitation increased during 1960–2012. Overall, occurrences of extreme precipitation are more concentrated in time. The weakening of the Asian summer monsoon strength and local topography had contribution to the variations of extreme precipitation over Yunnan. However, the forcing mechanisms are very complicated and need to be studied in subsequent work.